CROP WILD RELATIVES IN THE NORTHWESTERN BAIKAL REGION (ACCORDING TO THE MATERIALS OF THE 2014 COLLECTING MISSION) - M. O. Burlyaeva; D. A. Krivenko; S. G. Kazanovsky (Труды по прикладной ботанике, генетике и селекции)
The explorations carried out by a collecting team over the territory of the northwestern Baikal region made it possible to study the diversity of crop wild relatives (CWR) in 37 natural habitats in Bayandayevsky, Kachugsky, Zhigalovsky, Kazachensky-Lensky, Olkhonsky and Ekhirit-Bulagatsky districts of Irkutsk Province and the North Baikal district of the Republic of Buryatia. As a result, the areas richest in CWR species diversity were identified. Herbarium specimens and 102 seed and layering samples of 56 species from 23 genera representing wild relatives of fodder, legume, fruit, cereal and fiber crops were collected, including endemics listed in the Red Data Books of the Russian Federation, Irkutsk Province and the Republic of Buryatia.